Under 5 Children Mortality in Sudan: Situation Analysis - Abdeldafie, Selwa Y (International Journal of Innovative Research in Medical Science, 2018)
Sudan like other developing countries suffers a high mortality rate among under 5 children. Although there is an steady minimal reduction of this rate among Sudanese children but it is still high even after implementing many policies and interventions by the federal government. The aim of this work is to analyze the situation of under 5children mortality in Sudan in term of trend, causes of death, policies and interventions under taken to reduce this risk. Methods :the Sudan annual statistical report of 2015 was reviewed, it revealed that : the trend of under 5children mortality in Sudan is 70.10 as of 2015 and this is the lowest value while the highest one is 178.40 in the year 1960.There are a lot of policies under taken by the government to reduce this risk like : diarrhea community treatment , antenatal corticosteroids , postnatal care and IMCI implementation and the essential interventions which are implemented include :exclusive breastfeeding, skilled birth attendance, postnatal care, early initiation of breastfeeding , access to improved drinking- water sources, pneumonia care-seeking and pneumonia antibiotics.